2021
DOI: 10.3390/rs13122268
|View full text |Cite
|
Sign up to set email alerts
|

Multiscale Information Fusion for Hyperspectral Image Classification Based on Hybrid 2D-3D CNN

Abstract: Hyperspectral images are widely used for classification due to its rich spectral information along with spatial information. To process the high dimensionality and high nonlinearity of hyperspectral images, deep learning methods based on convolutional neural network (CNN) are widely used in hyperspectral classification applications. However, most CNN structures are stacked vertically in addition to using a onefold size of convolutional kernels or pooling layers, which cannot fully mine the multiscale informati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(18 citation statements)
references
References 47 publications
(48 reference statements)
0
18
0
Order By: Relevance
“…CNN. In the early days, a classic attempt to apply deep learning to RGB video was to extend 2D CNN to form a twostream architecture to obtain spatial features of video frames and motion features between frames, respectively [30][31][32]. An image is a projection from real-world 3D coordinates to 2D plane coordinates.…”
Section: Action Recognition Based On 3d Lightweight Multiscalementioning
confidence: 99%
“…CNN. In the early days, a classic attempt to apply deep learning to RGB video was to extend 2D CNN to form a twostream architecture to obtain spatial features of video frames and motion features between frames, respectively [30][31][32]. An image is a projection from real-world 3D coordinates to 2D plane coordinates.…”
Section: Action Recognition Based On 3d Lightweight Multiscalementioning
confidence: 99%
“…Their results showed that the proposed method performed better than the other HSI classification methods. In another study, Gong et al [55] proposed a multiscale squeeze-and-excitation pyramid pooling network (MSPN), and used a hybrid 2D-3D-CNN MSPN framework (which can learn and fuse deeper hierarchical spatial-spectral features with fewer training samples). The results demonstrated that a 97.31% classification accuracy was obtained based on the proposed method using only 0.1% of the training samples in their work.…”
Section: Existing Deficiencies and Future Prospectsmentioning
confidence: 99%
“…Each branch contains two modules, namely the pyramidal spectral block (the spectral attention) and the pyramidal spatial block (the spatial attention). To solve the limitation that the pyramidal convolutional layer has a single-size receptive field, Gong et al proposed a pyramid pooling module, which can aggregate multiple receptive fields of different scales and obtain more discriminative spatial context information [53]. The pyramid pooling module is mainly implemented by average pooling layers of different sizes, and then the feature map is restored to the original image size through deconvolution.…”
Section: Pyramidal Network Structurementioning
confidence: 99%